Expression, crystallization and structure elucidation of γ‐terpinene synthase from Thymus vulgaris. Issue 1 (1st January 2016) - Rudolph, Kristin; Parthier, Christoph; Egerer‐Sieber, Claudia; Geiger, Daniel; Muller, Yves A.; Kreis, Wolfgang; Müller‐Uri, Frieder
Abstract : The biosynthesis of γ‐terpinene, a precursor of the phenolic isomers thymol and carvacrol found in the essential oil from Thymus sp., is attributed to the activitiy of γ‐terpinene synthase (TPS). Purified γ‐terpinene synthase from T. vulgaris ( Tv TPS), the Thymus species that is the most widely spread and of the greatest economical importance, is able to catalyze the enzymatic conversion of geranyl diphosphate (GPP) to γ‐terpinene. The crystal structure of recombinantly expressed and purified Tv TPS is reported at 1.65 Å resolution, confirming the dimeric structure of the enzyme. The putative active site of Tv TPS is deduced from its pronounced structural similarity to enzymes from other species of the Lamiaceae family involved in terpenoid biosynthesis: to (+)‐bornyl diphosphate synthase and 1, 8‐cineole synthase from Salvia sp. and to (4 S )‐limonene synthase from Mentha spicata .